1982
DOI: 10.1088/0022-3727/15/6/017
|View full text |Cite
|
Sign up to set email alerts
|

Theory of open-circuit photovoltage decay in a finite base solar cell with drift field

Abstract: A theory of open-circuit photovoltage decay has been developed in a pn junction solar cell by using the Sturm-Liouville R-transform technique. The theory accounts for finite thickness of the base, drift field in the base and a finite surface recombination velocity at the back surface. The theory is applied to analyse some experimental results on photovoltage decay in a solar cell induced by monochromatic light. A good fit is obtained between the theoretical and the experimental results which gives an estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…To our knowledge this is the first study of the open-circuit voltage decay transient in DE Si and we demonstrated the possibility of exponential decay of V oc (t). However, the results in figure 2 are different from those observed in some dislocation-free solar cells with a linear decrease in V oc (t) after the illumination is switched off [21][22][23][24]:…”
Section: Open-circuit Voltage Decaycontrasting
confidence: 64%
See 1 more Smart Citation
“…To our knowledge this is the first study of the open-circuit voltage decay transient in DE Si and we demonstrated the possibility of exponential decay of V oc (t). However, the results in figure 2 are different from those observed in some dislocation-free solar cells with a linear decrease in V oc (t) after the illumination is switched off [21][22][23][24]:…”
Section: Open-circuit Voltage Decaycontrasting
confidence: 64%
“…It is found [11][12][13][14][15][16][17] that V oc can decay according to the exponential function. However, in some dislocation-free solar cells V oc is found [21][22][23][24] to decrease linearly with time after the illumination is switched off.…”
Section: Introductionmentioning
confidence: 99%
“…Open-circuit voltage decay measurements were also performed as shown in Figure b. Under open-circuit conditions, charges build up under illumination and longer charge lifetimes signify a pronounced reduction in carrier recombination as seen in the case when P3HT was used.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Finally, it may be remarked that we tried to make a quantitative comparison between this theory and the experimental results of Madan andTewary (1983, see also Sharma andTewary 1982). We fixed the parameters of the base as obtained by Sharma and Tewary (1982) and varied the parameters of the diffused layer in order to get the leastsquare fit with the experimental results.…”
Section: Effect Of D On Pvdmentioning
confidence: 99%
“…Theories of open-circuit photovoltage decay (PVD) obtained after a rapid termination of illumination in a pn junction solar cell have been given recently by Jain (1981), Dhariwal and Vasu (1981), Joshi and Singhal (1982), Murlidharan et a1 (1982) and Sharma and Tewary (1982). In all these theories the effect of the front diffused layer (emitter) on the PVD has been neglected.…”
Section: Introductionmentioning
confidence: 99%